Autoimmune cerebellar ataxia with initial seronegativity and low‐titer anti‐glutamic acid decarboxylase antibody in the cerebrospinal fluid. Issue 2 (4th May 2017) - Sato, Kenichiro; Arai, Noritoshi; Bannai, Taro; Kodama, Satoshi; Omori‐Mitsue, Aki; Hida, Ayumi; Takeuchi, Sousuke
Abstract: Background: In cases with anti‐glutamic acid decarboxylase (GAD) antibody‐positive cerebellar ataxia, the titer of the antibody is usually very high. However, a few cases of low‐titer GAD antibody‐positive cerebellar ataxia patients have been described recently. In such patients, the antibody has been detected predominantly in serum, rather than in cerebrospinal fluid. Case presentation: A 34‐year‐old man presented with subacute‐onset cerebellar ataxia, and examinations revealed no abnormal findings except low‐titer anti‐GAD antibody in the cerebrospinal fluid at initial evaluation: the serum antibody became slightly positive in a delayed manner. Treatment with steroid and/or immunoglobulin was effective in improving symptoms, and the effect of these treatments continued for approximately 1 year. Conclusions: The present case suggested a potential diagnostic pitfall, in which the examination of serum anti‐GAD antibody at initial evaluation alone might be insufficient to rule out this disease. It may be indicated that the routine screening should include examination for the GAD antibody in both the serum and cerebrospinal fluid, plus additional follow‐up checks for the antibody in the subsequent clinical course. Care must be taken to avoid non‐detection of this disease with possibly reversible symptoms in patients with cerebellar ataxia of unknown origin. Abstract : A case of 34‐year‐old man presenting with low‐titer GAD‐Ab positive cerebellar ataxia (AGCA), who on initial evaluation showed elevated GAD‐Ab in the CSF but not in the serum, and his serum titer elevated in a delayed manner. It may be indicated that routine screening for adult‐onset acute or subacute cerebellar ataxia should include examination for GAD‐Ab in both serum and CSF, plus additional follow‐up checks for the antibody in the subsequent clinical course.